Distribution of Virulence Genes and Sequence-Based Types Among Legionella pneumophila Isolated From the Water Systems of a Tertiary Care Hospital in India - Sreenath, K.; Chaudhry, Rama; Vinayaraj, E. V.; Dey, A. B.; Kabra, S. K.; Thakur, Bhaskar; Guleria, Randeep (Frontiers in Public Health, 2020)
Background: Legionnaires' disease (LD) is a potentially fatal pneumonia predominantly caused by infection due to Legionella pneumophila although more than 50 other Legionella species are described. Water systems contaminated with Legionella spp. are the implicated sources of Legionnaires' disease. In this study, we aimed to assess Legionella contamination in the water sources of a tertiary care hospital and to determine the virulence properties and molecular characteristics of L. pneumophila environmental isolates. Methods: During May 2015 through August 2018, a total of 201 hospital water samples were tested for L. pneumophila by standardized culture procedures; environmental isolates were examined for the presence of two virulence genes: Legionella vir homolog (lvh) and repeats in structural toxin (rtxA) by PCR. The genotyping of isolates was performed by sequence-based typing (SBT) according to the protocol of the European Study Group for Legionella Infections (ESGLI). Results:L. pneumophila was isolated from 38/201 (18.9%) water samples; among the 46 isolates, the lvh locus was present in 45 (97.8%), the rtxA locus was found in 45 (97.8%), and both loci were found in 44 (95.7%) isolates. A total of 23 sequence types (STs) were identified among the 44 isolates (index of discrimination [IOD] of 0.929), and 11/23 (47.8%) STs were new to the ESGLI database. Conclusions: The study results showed genetic diversity in L. pneumophila isolates from the hospital environment along with a high percentage of pathogenicity loci. Besides, certain STs may have an increased ability to cause legionellosis, thus requires specific infection control and prevention strategies whenever identified.